The humanitarian space in peril - how do recent political developments affect the work of international relief NGOs - Henghuber, Heinz (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The 'humanitarian space' of relief NGOs is more than ever endangered. Many political developments, such as belligerent military doing aid work, deliberate targeting of aid workers or politicisation of aid, are not new, but accelerating, aggravating trends. They are challenging how international relief NGOs work today and how they will work in the future. Humanitarian aid agencies are forced to adjust and position to the increasing complexity of this environment.